PENGARUH KONSUMSI REBUSAN DAUN SELEDRI DAN PISANG AMBON TERHADAP HIPERTENSI PADA MASA PERIMENOPAUSE DI PUSKESMAS PATIA TAHUN 2025 - Daswi, Daswi; Agus Santi Br. Ginting; Salfia Darmi; Yuni Yuliatami; Iin Rapitiani; Atik Nurindah Sari; Eneng Ifat Fatmawati; Dede Rohimah (Journal of Innovation Research and Knowledge, 2025)
Stress can contribute to hypertension in perimenopausal women. During the perimenopausal transition, many women experience vasomotor symptoms that can affect their daily activities. Complementary therapies are currently gaining popularity in addressing health issues. Celery and Ambon bananas are natural ingredients that contain nutrients that support this effort. This study aims to determine the effectiveness of boiled celery leaves and Ambon bananas in lowering blood pressure in perimenopausal women. The method used was a qualitative research approach with a descriptive case study approach. Twelve perimenopausal women were divided into two intervention groups. Group A was given 200-300 ml of boiled celery leaves every morning for 7 days, while Group B was given 200-300 grams of Ambon bananas every morning for 7 days. The results showed that the celery leaf decoction group (16.7 mmHg) was greater than the Ambon banana group (14.2 mmHg), with a difference of 2.5 mmHg. Similarly, the diastolic decrease in the celery leaf decoction group (13.3 mmHg) was greater than the Ambon banana group (10.0 mmHg), with a difference of 3.3 mmHg. These two interventions can complement each other, where the celery leaf decoction acts as a fast therapy (short-acting) and the Ambon banana functions as a maintenance therapy (long-acting). It is recommended that perimenopausal women regularly consume celery leaf decoction and banana fruit as a natural alternative to help control blood pressure, accompanied by a balanced diet and a healthy lifestyle